Effects of COVID-19 on Substance Use in Singapore - Ho Teck Tan; Boon Ceng Chai; Yit Shiang Lui (SAGE Publishing, 2021)
This review examines the impact of COVID-19 on the substance-abuse landscape and climate with particular attention on Singapore's. Substance-abuse has received the least attention during the COVID-19 outbreak and this pandemic has further sheared the problem's visibility and the provision of care for this population of sufferers. The authors examine the current literature to look at the access and utility of street drugs due to border closure, the influence of the pandemic on prevailing drug behaviours as well as the effect of social distancing on drug-users. Two case studies are described. The paper serves to illuminate the ever-present problem of substance-abuse even during a viral pandemic and to remind the local government and healthcare system to continue efforts in caring for this group of patients.